Synthesis and characterisation of polymer-anchored oxidovanadium(IV) complexes and their use for the oxidation of styrene and cumene - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (European Journal of Inorganic Chemistry, 2007)
{The Schiff bases H(2)fsal-ea (I), H(2)fsal-pa (II) and H(2)fsal-amp (III), derived from 3-formylsalicylic acid and 2-aminoethanol, 3-aminopropanol and 2-amino-2-methylpropanol, respectively, have been connected, by means of covalent bonds, to chloromethylated polystyrene cross-linked with 5% divinylbenzene. On treatment with [
Keywords: dissolution rate; mass transfer coefficient; particle size distribution; polydisperse solid; reactive liquid